Public Engagement and Oversight for Accountable Governance in Corruption Prevention Efforts in North Sulawesi Province - Ressy Mewengkang; Brain Fransisco Supit; Djoly Vekky Warokka (Academy of Education Journal, 2026)
This study aims to analyze the condition of accountable regional governance in North Sulawesi Province, focusing specifically on the dimension of engagement and oversight by all employees and the public, one of the six key issues measured in the Integrity Assessment Survey. The study employed a descriptive qualitative approach through semi-structured interviews with three key informants representing different levels of position, namely the Provincial Secretary, the Head of the Human Resources Development Agency, and a staff member of the North Sulawesi Provincial Social Affairs Office, supplemented by a review of secondary data on Integrity Assessment Survey scores for the 2023 to 2025 period. Data were analyzed thematically and interpreted through the lens of public accountability and good governance. Based on the three-zone categorization framework commonly used to interpret the Integrity Assessment Survey index scale, the engagement and oversight dimension score for North Sulawesi Province fell within the vulnerable-to-risk zone at 73.05 in 2023, remained in that zone with an increase to 76.10 in 2024, but declined to the at-risk zone at 72.61 in 2025. The findings show that formal complaint channels are available and reasonably actively used at the level of regional secretariat leadership, yet their dissemination has not evenly reached operational staff, while fear of retaliation and the absence of clear whistleblower protection mechanisms tend to make participation among lower-level employees passive. Public participation in overseeing public services also remains limited due to the perception that government responses to complaints are slow. This study recommends expanding the dissemination of complaint channels to all levels of the civil apparatus, strengthening whistleblower protection guarantees, and developing more responsive public feedback mechanisms as strategic steps to strengthen the accountability of regional governance in North Sulawesi Province.